Spatial and temporal evolution characteristics of meteorological drought in the Northwest of Yellow River Basin and its response to large-scale climatic factors. Issue 12 (3rd November 2022) - Fu, Yinghao; Shen, Xiaojing; Li, Wangcheng; Wu, Xu; Zhang, Qingqing
Abstract: The Northwest of Yellow River Basin (YRB) is an arid and semi-arid region. This study employs wavelet analysis, dry area coverage, drought frequency, and Mann–Kendall test trend to investigates the evolution characteristics of drought in the Northwest of YRB and the impact of macro climatic conditions on drought. The scale of season and year Standardized Precipitation Evapotranspiration Index (SPEI) was mostly represented as alternating dry and wet weather in this region. SPEI decreased significantly in each season, indicating increased drought. The drought situation changed abruptly in 1968, and the change was more obvious around 2000. Drought trend in autumn is more noticeable than in the other three seasons. The average annual dry area covers 34%. The drought frequency in each station at the annual scale was between 30.78% and 46.15%, its high values are mainly concentrated in the western region. The main cycles of annual SPEI changes are 37 and 5 years; spring is 45 and 10 years; summer is 20 and 5 years; autumn is 36, 10, and 5 years; winter is 45, 22, and 5 years. Furthermore, drought occurrence and changes are closely related to large-scale climatic factors, with El Niño-Southern Oscillation having the greatest impact on drought. HIGHLIGHTS: Calculation of multi-scale SPEI based on the Penman–Montieth model. Employing Morlet wavelet analysis, dry area coverage, drought frequency, Mann–Kendall sudden change examination, and other methods to conduct a qualitative and quantitative analysis of the region's spatial and temporal distribution of drought. Using cross-wavelet analysis and wavelet coherence analysis to enhance the research of the response of drought to large-scale climatic influences. Graphical Abstract